THE CORRELATION BETWEEN STUDENTSâ€™ READING COMPREHENSION AND THEIR PARAPHRASING ABILITY IN NARRATIVE TEXT - Swarini, Ade Resky; Bharati, Dwi Anggani Linggar; Sutopo, Djoko (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2018)
Paraphrasing activity allows the students to interpret what they have understoodfrom the text in reading activity. This study investigates the correlation of thestudentsâ€™ reading comprehension and their paraphrasing ability in narrative text.There are two hypotheses in this research; null hypothesis (Ho) and the alternativehypothesis (Ha). The null hypothesis says â€œThere is no correlation between studentsâ€™reading comprehension and their paraphrasing ability in narrative textâ€. Then, Hasays â€œThere is a correlation between studentsâ€™ reading comprehension and theirparaphrasing ability in narrative textâ€.The population of this study is the eleventh graders of SMAN 1 Ambarawa in theacademic year of 2016/2017. The students of XI MIPA 5 are taken as the samples.The design of this study is explanatory research design. The data are gained byadministering two kinds of tests; reading comprehension and paraphrasing tests.Those tests are administered twice by using two different texts. There are three mainprocesses in applying this method in the study; the use of the scatterplot, Pearsonproduct moment coefficient, and correlation coefficient interpretation. Scatterplotsdisplays that there is a positive linear relationship. Then, the data are calculated byusing the Pearson product moment to know the degree of relationship among thevariables. The results of the computation of correlation coefficient applied to thesample are 0.67 and 0.84. The consultation to the critical value of the r ProductMoment with 95% confidence level and the number of the subjects 32 is 0.349. Itmeans that the results obtained from the computation are higher than its criticalvalue. Next, the results of the computation of correlation coefficient are consulted tothe criteria of correlation coefficient interpretation. The interpretations of therelationship are substantial and high to very high. It can be concluded that there is asignificant positive relationship between studentsâ€™ reading comprehension ability innarrative text (X) and their paraphrasing ability in narrative text (Y) on the eleventhgraders of SMA Negeri 1 Ambarawa in the academic year of 2016/2017.